Avaliação do potencial de remoção de arsênio utilizando lemna minor L. (1753) - Gimenes, Luana Lorca Sartoris (2015)
Arsenic is one of the most toxic known inorganic contaminants, even in small concentratios, and many problems can occur with human exposure to it. Thus, the use of suitable technologies and at low cost becomes essential to remove this contaminant from the environment. One promising technique is the phytoremediation that is gaining more attention in the scientific community once it has ease of deployment and resistance of plants to capture or simply neutralize the action of certain toxic compounds of water, serving as a true “green” filter. This study aims to evaluate the efficiency of the macrophyte Lemna minor on the removal of arsenic, verifying the selectivity of the plant to its inorganic species (As III and As V) and the best removal time. For the experiments, healthy plants (approximately 0,5 g fresh weight) were selected and transferred to beakers containing different concentrations of arsenic forms (50; 100; 200; 300; 400 and 500 μg L-1) in Steinberg diluted nutrient solution (50%). The concentrations in the water and plant biomass were determined using an Atomic Absorption Spectrometer for Flame, with hydrides generating. Through the determination of As (III) in the solution containing the Lemna minor up to 64 hours, there was a gradual decrease of the absorbance signal in the solution within 48 hours. At all concentrations tested removal rates obtained percentage than 50%, increased compared with the initial concentration. Lemna minor was effective for removal of As (III) of the solution at all concentrations and under the conditions studied as having greater removal rate in the 48 hour period. In its dry biomass was noticed highen accumulation of the highest concentrations tested, then the removal is more efficient when it is exposed to higher concentrations of the contaminant. As for the As (V) no removal solution efficiency in all tested concentrations and also analysis of the dried biomass of these plants showed no accumulation of high concentration in tissue. This result demonstrates a selective potential of the plant for the removal of As (III), the most toxic species can be employed to determine / selective removal of arsenic.